Temperature and dependence of photoconductivity and structures Mn4 Si 7-Si Mn-Mn4 And7 (Texas Journal of Engineering and Technology, 2022)
This article studies the effect of infrared radiation and temperatureson the parameters of higher manganese silicides on the surface of silicon created on the basis of impurity atoms of manganese. The possibility of creating effective thermocouples and photodetectors based on the structures of SixMn1-xSi- MnxSi1-x is shown